PEMANFAATAN SITUS PURBAKALA CANDI MUARO JAMBI SEBAGAI OBJEK PEMBELAJARAN SEJARAH LOKAL DI ERA DIGITAL - M. Afrillyan Dwi Syaputra; Sariyatun Sariyatun; Deny Tri Ardianto (Jurnal Pendidikan Sejarah Indonesia, 2020)
This study aims to analyze the use of Muaro Jambi temple site as an object of local history learning in the digital era. The problems discussed in the article are: (1) How does the Muaro Jambi Temple can be used as local history object of study? (2) How does the Muaro Jambi Temple could be used as the object of local history learning in digital era? To answer the two problems, authors conducted literature study method by collecting several articles from research results related to the research theme. Data collection is done by analyzing the source documents and literature. The results of this study indicate that the use of historical relics in the surrounding environment can lead to effective learning, coupled with the application of local history learning material using interactive media that follows the times, such as videos, digital books, and the internet. In addition to giving rise to effective, interesting, and interactive learning, of course, the purpose of this utilization is to increase historical knowledge of learners, especially on local historical material.